Multilocular infection caused by hypervirulent Klebsiella pneumoniae - Tyll, T; Novotný, D; Beran, O; Bartáková, E; Pudil, J; Králová Lesná, I; Rára, A (Epidemiologie, mikrobiologie, imunologie, 2023)
Hypervirulent strains of Klebsiella pneumoniae (hvKP) can cause atypical multilocular infections in otherwise healthy patients. Diagnosis of infection caused by hvKP is based mainly on clinical findings and laboratory results, including detection of virulence genes. It typically manifests as hepatic abscess with metastatic spread. Treatment is based on surgical intervention in combination with targeted antimicrobial therapy. The occurrence of hvKP infection is relatively common in Asia, and while still rare in Europe, incidence is increasing. The article aims to provide a short overview of the issue and increase awareness of the possible occurrence of hvKP infections.
Keywords: Klebsiella Infections; Humans; virulence; hypervirulent; lidé; Anti-Bacterial Agents; faktory virulence; Virulence; Evropa; sepsis; Klebsiella pneumoniae; sepsis mimics; infekce bakteriemi rodu Klebsiella; amputation; Virulence Factors; Europe; antibakteriální látky; soft tissue infection; inflammatory parameters